Sindrom Misogini Dalam Cerpen “Wah Wah Wah’ Karya Tsi Taura: Analisis Psikologi Sastra - Lela Erwany; Rosliani Rosliani; Dardanila Dardanila (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
Short stories as part of literature are the universe of reality in which there are events experienced by the actors. In the short story Wah Wah Wah, it can be seen the presence of a psychological phenomenon experienced by the main character. The psychological phenomenon was studied using a literary psychology approach and misogyny. The method used is a qualitative method with a hermeneutic approach. This approach is considered capable of maintaining the authenticity of the text. The results of this study indicate that the misogyny contained in the Wah Wah Wah short story is caused by trauma or the treatment of his wife, children, and daughter-in-law to the character Si Aku. Before marriage he did not hate women. This can be seen from his attitude towards his dead mother. He didn't hate his mother. Due to chronic misogyny, eventually gradually turned into a permanent mental disorder. This is because there is no treatment from a psychologist and family support. He experiences stress and his soul is disturbed or crazy.